Heat Resistance of Clostridium botulinum Types A and B Spores on Beef Subjected to Dry Heat by Oven - NOHARA, Hideo; OKUBO, Ryoko; KOMAKI, Masaru; NUMATA, Masahiro; SUZUKI, Miki; MORIOKA, Yutaka; MATSUDA, Norihiko; ARAKI, Miho (Japanese Journal of Food Microbiology, 1996)
Heat resistance of Clostridium botulinum types A and B spores on the beef surface subjected to dry heat in an electric oven were examined. The standard heat resistance (D121°C and z value) of the spores in 0.067 M phosphate buffer (pH 7.0) were 0.63 min and 10.7°C for types A, and 0.24 min and 9.4°C for types B, respectively. Surface temperature of beef cubes was measured in oven at 270°C.The temperature reached to 100°C for 25 min and maintained until 40 min. Then, it began to rise again and reached to 130°C for 60 min. Types A and B spores inoculated on the surface of raw beef cubes (105 CFU/cm2) were subjected to dry heat at 250, 270 and 300°C. However there was no difference in the decreasing tendency of the numbers of both types A and B spores among heating temperature. Also these numbers gradually decreased with heating time and were below 10 CFU/cm2 within 40 min. D values of both spores on each heating temperature were 8.3-11.1 min. Beef cubes were heated at 270°C with 1, 3 or 5% (w/w) salt on their surface and incubated at 30°C for a month. The production of toxin in cubes were restricted by hard heat treatment and high salt concentration. This effect was more sensitive for types B spores.